Animals in Saami Shamanism: Power Animals, Symbols of Art, and Offerings - Äikäs, Tiina (Religions, 2021)
In this paper, we study the role of power animals in contemporary Saami shamanism and how past and present are entwined in the presentation of power animals. In the old Saami worldviews, in addition to animals, spirits and sacred rocks (sieidi, SaaN) were also considered to be able to interact with people. Animals were an important part of offering rituals because livelihood and rituals were intertwined. Past “religions” are used as an inspiration for contemporary shamanistic practices, in line with one of late modernity’s core concepts, namely creativity. Present-day shamanistic practices can be described as ritual creativity, and they combine traces of old and new ritual activities. At the shamanistic festival Isogaisa, organized in northern Norway, these different roles of animals and ritual creativity become evident. Here, animals appear as spirit animals, as well as decorative elements on drums and clothes and as performance. In this paper, we combine material culture studies, interview data, and participatory observations in order to reflect the meanings and use of power animals in contemporary spiritual practices. How are traces of the past used in creating contemporary spirituality? How are animals and their artistic presentations entangled in contemporary shamanism?